Agrochemical Characteristics of Newly Developed Light Sierosem of the Fergana Valley - Yuldashev G; Makhramkhuzhaev S (Zien Journals, 2023)
The current state, agrochemical and soil-reclamation conditions of light sierozems in the North of the Fergana Valley are considered. The questions of the structure of the soil profile, the state of drainage and the effect of irrigation on the change in agro-chemical properties, morphological features of the studied gray soils are considered. It is shown that for a short period of 2-3 years under irrigation conditions when cultivating medicinal plants such as lavender in light gray soils. Taking into account the washout, there is a slight improvement in the properties of the washed-out part of the light gray soils.
Keywords: agro chemistry; valley; light gray soil; humus